Dual-Balloon–Assisted Coil–Onyx Embolization with Intraprocedural Management of Onyx Reflux for a High-Flow Direct Carotid–Cavernous Fistula: A Technical Case Report - Yahya Assegaff; Erwin Hardiansyah; Rani Kerinciani Adam; Zhongwei Xu; Kai Qiu; Linbo Zhao; Sheng Liu (Neurointervention Working Group of Indonesian Neurological Association, 2026)
Highlight: Proximal BGC inflation enables superselective angiography to localize the fistula Distal ICA balloon blocks antegrade flow, reducing the risk of Onyx reflux Proximal BGC arrests Onyx reflux and enables aspiration to preserve ICA patency ABSTRACT Introduction: High-flow direct carotid–cavernous fistulas (CCFs) are most commonly caused by traumatic injury to the cavernous segment of the internal carotid artery (ICA). During balloon-assisted coil–Onyx embolization, reflux of Onyx into the ICA remains a persistent technical challenge, as it carries a risk of intracranial arterial occlusion and potentially severe neurological sequelae. Case: A 58-year-old man came with progressive right-sided proptosis, chemosis, orbital bruit, and diplopia following head trauma. Digital subtraction angiography (DSA) confirmed a high-flow traumatic direct CCF (Barrow Type A). Dual-Balloon flow control was performed using a distal ICA protective balloon positioned across the fistulous orifice and a proximal balloon guide catheter (BGC) placed in the cervical ICA. Coil framing was performed, followed by controlled injection of Onyx-18. Minor Onyx reflux into the ICA was managed by BGC inflation to arrest antegrade flow, thereby preventing intracranial embolization, and aspirating the refluxed Onyx via an intermediate catheter. Final angiography demonstrated complete fistula occlusion with preserved ICA flow, and symptoms improved significantly within 48 hours. Conclusion: Dual-balloon-assisted coil–Onyx embolization represents an effective reconstructive strategy for high-flow direct CCFs, particularly in mitigating the risk of Onyx reflux. The proximal BGC serves as a critical